Perancangan Interior ROG Gaming Center di Surabaya - Stevanus Felix; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2018)
The background of this design is the gamers need of a place where various facilities and commercial area for gaming products are available. Besides, the gaming center is also able to accommodate the gamers and gaming products in a tournament or E-Sports competition. The design purpose of ROG Gaming Center in Surabaya is to accommodate, facilitate, gather gamers and E-Sports athletes, as well as hold events such as national to international level of tournament and E-Sports competition. At the same time, this design can also improve people knowledge about E-Sports.